Fischer–Tropsch synthesis of olefin-rich liquid hydrocarbons from biomass-derived syngas over carbon-encapsulated iron carbide/iron nanoparticles catalyst. (1st April 2017) - Lu, Yongwu; Yan, Qiangu; Han, Jun; Cao, Baobao; Street, Jason; Yu, Fei
Highlights: Direct conversion of biosyngas to olefin-rich liquid hydrocarbons was reported. Carbon-encapsulated iron carbide/iron catalyst showed high selectivity to olefins. The formation mechanism of carbon-encapsulated iron carbide/iron was proposed. The iron carbide/iron core of catalyst consisted of α-Fe, θ-Fe3 C, and Fe15.1 C. Abstract: Olefins are extensively used in the chemical industry as building blocks for manufacturing a wide range of products such as polymers, drugs, cosmetics, solvents, and detergents. Traditionally, olefins have been produced from thermal or catalytic cracking of petroleum-derived hydrocarbons, but environmental and economic concerns are urging exploration of alternative routes for their production from renewable sources. Herein, we report the synthesis of olefin-rich liquid hydrocarbons from biomass-derived syngas (biosyngas) via Fischer–Tropsch reaction by using carbon-encapsulated iron carbide/iron nanoparticles (CEICINs) catalysts. The CEICINs core-shell nanostructured catalysts typically constituted iron carbide/iron-core diameters of 6–30 nm and graphite-shell thickness of 2–5 nm, where the iron carbide/iron-core consisted of α-Fe, θ-Fe3 C and Fe15.1 C. The catalytic performance over CEICINs at mild reaction conditions (310 °C, 1000 psig, 3000 h −1 ) showed that CO and H2 conversion was ∼87.5% and 85%, respectively. The C5+ liquid hydrocarbon selectivity was ∼65%, ∼44.8% of which was olefins. The liquid product formation rate was 0.12 g/(gcat h) during the time-on-stream of 100 h after achieving steady state. The volume percent of the oil phase in the liquid product was ∼60%. The higher reaction temperature led to the higher selectivity towards olefins, while the effect of biosyngas pressure was not a significant factor concerning olefin selectivity. Gas hourly space velocity (GHSV) had a negative effect on the formation of olefins due to the short-time contact of the reactant gas with the CEICINs catalyst. This work demonstrated the technical feasibility of the direct synthesis of olefin-rich liquid hydrocarbons by utilizing CEICINs catalysts from biosyngas via biomass gasification, biosyngas cleaning, and Fischer–Tropsch synthesis technology.